Fishes of the Indian Ocean and Red Sea - Taquet, Marc; Taquet, Marc; Diringer, Alain (Editions Quae, 2012)
This guide, illustrated by more than 1,500 underwater photographs, presents nearly 1,200 species of fish in the Indian Ocean and Red Sea. The reference work dedicated to enthusiasts of the undersea world, more especially divers, will also be of interest to a wide audience that is curious about Nature and its riches.